Vitamina D y salud ósea (2005)
ABSTRACT: Vitamin D plays an essential role in calcium homeostasis and bone health, however researches during last years have elucidated other biological actions of its active form 1,25-Dihydroxyvitamin D (1,25 (OH2) D3 (D2)) on target cells. This vitamin is considered as a hormone too, because it is produced and metabolized to the active form that is able to induce through its nuclear receptor, target gene transcription, which are responsibles for maintenance of serum calcium at the physiological level and the bone health. Finally, this review proposes that consuming a balanced diet along with the suitable sunlight exposure, it coul be a preventive strategy to decrease risk of bone pathologies and to maintain normal physiological level of vitamin D. In humans vit D can be affected by nutritional, environmental, physiological and cultural factors.